Performance trends of millimeter wave energy harvesting networks with base station cooperation. - Mohd. Noor, Anis Syahira (RMP Publications, 2023)
The great demand for high data rate transmission has evolved due to the booming wireless services, especially on the forthcoming fifth generation (5G) network. The upcoming cellular network is expected to utilize the higher segment of the frequency band, i.e., the millimeter wave (MMW), to meet the demand for extraordinarily high data rates to serve abundant applications. This paper focuses on developing a prediction tool for assessing the energy coverage of the downlink transmission in MMW energy harvesting networks with base station cooperation based on the stochastic geometry model. The signal-to-noise plus interference ratio (SINR) and energy coverage are evaluated by modeling the user and base station locations following the Poisson Point Processes (PPP). Joint transmission of two base stations is considered to investigate its impact on energy harvesting. The prediction tool is developed using MATLAB, where the unique characteristics of MMW propagation and antenna features are incorporated into the simulations. It is observed that the dense deployment of the MMW base station significantly improves both the SINR and energy coverage.